Kajian Kriminologis terhadap Kejahatan Pencurian Besi Rel Kereta Api di Wilayah Lampung Selatan - Daan Hafids Zahidien; A Irzal Fardiansyah; Fristia Berdian Tamza (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Theft of railroad rails in South Lampung is a crime that threatens the safety of transportation and public services. This study aims to analyze the factors that cause this crime and examine the prevention efforts that have been made. The method used is an empirical approach through literature studies and interviews with the police, perpetrators of crime, and academics. The results of the study show that theft is triggered by socio-economic factors such as poverty, unemployment, lack of family supervision, and negative social environmental influences. Lack of legal understanding and easy access to crime information also worsen the situation. Prevention efforts are carried out through three approaches: pre-emptive (legal education and social development), preventive (supervision and protection of infrastructure), and repressive (law enforcement). Collaboration between the community and law enforcement officers is the main key to preventing and overcoming this crime in a sustainable manner.